2010
DOI: 10.1111/j.1365-3040.2010.02130.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of pre‐anthesis anther sink strength for maintenance of grain number during reproductive stage water stress in wheat

Abstract: Reproductive stage water stress leads to spikelet sterility in wheat. Whereas drought stress at anthesis affects mainly grain size, stress at the young microspore stage of pollen development is characterized by abortion of pollen development and reduction in grain number. We identified genetic variability for drought tolerance at the reproductive stage. Drought-tolerant wheat germplasm is able to maintain carbohydrate accumulation in the reproductive organs throughout the stress treatment. Starch depletion in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
254
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 320 publications
(297 citation statements)
references
References 75 publications
29
254
1
4
Order By: Relevance
“…By employing the inter auricle distance as a phenotypic marker and imposing 3-4 days of cold or drought stress (Oliver et al 2005(Oliver et al , 2007Ji et al 2010), young microspore and bi-nucleate pollen stage were targeted. However, tetrad formation and early microspore generation has also been identified to be most sensitive to cold stress (Nishiyama 1970(Nishiyama , 1976.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By employing the inter auricle distance as a phenotypic marker and imposing 3-4 days of cold or drought stress (Oliver et al 2005(Oliver et al , 2007Ji et al 2010), young microspore and bi-nucleate pollen stage were targeted. However, tetrad formation and early microspore generation has also been identified to be most sensitive to cold stress (Nishiyama 1970(Nishiyama , 1976.…”
Section: Resultsmentioning
confidence: 99%
“…Microsporogenesis, the highly sensitive stage to heat stress (Matsui et al 2000), has not been studied extensively due to the lack of a precise phenotypic marker. However, a marker based on inter auricle distance has been identified for cold stress phenotyping (Satake and Hayase 1970), and extended to quantify the impact of cold (Oliver et al 2005(Oliver et al , 2007 and drought stress (Ji et al 2010;Liu and Bennett 2011) during young microspore and bi-nucleate pollen stages. The classic work by Satake and Hayase (1970) used different inter auricle distances and stress exposure duration to examine just two contrasting rice entries, indicating the challenge in identifying a robust marker that could be used across many genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…In maize under water stress, functional reversion analysis by sucrose feeding (see Boyer and McLaughlin 2007) confirmed the role of glucose in floral abortion and identified a cell wall and a soluble invertase among the few genes controlling sugar uptake by the ovary. In wheat, Ji et al (2010) observed a difference in storage carbohydrate accumulation in drought-sensitive and drought tolerant wheat. Interestingly, genotypic variation for WSC accumulation in the stem, mainly fructans, is well established in wheat (Rebetzke et al 2008;Dreccer et al 2009) and consistent with different levels of expression in fructan metabolism enzymes (Xue et al 2008).…”
mentioning
confidence: 91%
“…Under drought, carbohydrate metabolism enzymes play a crucial role in grain set in tolerant maize germplasm (Boyer and McLaughlin 2007) and pollen viability in wheat (Ji et al 2010). In maize under water stress, functional reversion analysis by sucrose feeding (see Boyer and McLaughlin 2007) confirmed the role of glucose in floral abortion and identified a cell wall and a soluble invertase among the few genes controlling sugar uptake by the ovary.…”
mentioning
confidence: 99%
“…Drought during the pre-anthesis stage of reproductive development has a dramatic effect on grain number (Fig. 1a-c;Bingham 1966;Fischer 1973;Ji et al 2010). Even short, mild water stress periods at the young microspore stage of pollen development (Fig.…”
Section: Drought Stressmentioning
confidence: 99%